Fecal Microbiota Transplantation (FMT) as an Adjunctive Therapy for Depression—Case Report - Doll, Jessica P. K.; Vázquez-Castellanos, Jorge F.; Schaub, Anna-Chiara; Schweinfurth, Nina; Kettelhack, Cedric; Schneider, Else; Yamanbaeva, Gulnara; Mählmann, Laura; Brand, Serge; Beglinger, Christoph; Borgwardt, Stefan; Raes, Jeroen; et al. (Frontiers in Psychiatry, 2022)
Depression is a debilitating disorder, and at least one third of patients do not respond to therapy. Associations between gut microbiota and depression have been observed in recent years, opening novel treatment avenues. Here, we present the first two patients with major depressive disorder ever treated with fecal microbiota transplantation as add-on therapy. Both improved their depressive symptoms four weeks after the transplantation. Effects lasted up to eight weeks in one patient. Gastrointestinal symptoms, constipation in particular, were reflected in microbiome changes and improved in one patient. This report suggests further FMT studies in depression could be worth pursuing and adds to awareness as well as safety assurance, both crucial in determining the potential of FMT in depression treatment.